Peningkatan Efektivitas Pengelolaan Data Obat melalui Integrasi Rekam Medis Elektronik Berbasis Farmakovigilans di Fasilitas Kesehatan Primer - Gemy Nastity Handayany; Trimaya Cahya Mulat; Devita Rahayu (Jurnal Pendidikan Indonesia, 2026)
Digital transformation in healthcare is driving the adoption of Electronic Medical Records (EMR) as a means to improve service quality and patient safety. One challenge still faced in primary healthcare facilities is suboptimal medication data management, such as recording errors, duplicate prescriptions, and delays in reporting adverse drug reactions. Therefore, integrating EMRs with pharmacovigilance systems serves as a strategic solution to improve the effectiveness of medication data management. This community service initiative aims to enhance healthcare workers’ knowledge and skills in using pharmacovigilance-based EMRs. The method employed is a participatory educational approach through stages of health education, training, interactive discussions, and mentoring. The activity was conducted at a community health center in Makassar City in February 2026, involving 25 participants comprising doctors, nurses, pharmacists, and Health Information Management (HIM) staff. Evaluation was conducted through pre- and post-tests, practice observations, and participant satisfaction questionnaires. The results of the activity showed an increase in participants’ knowledge from an average score of 54.4 to 86.3, representing a 31.9% increase. Additionally, there was a significant improvement in practical skills, particularly in medication data entry (92%), identification of drug interactions (84%), reporting of adverse drug reactions (80%), and use of system alert features (88%).